The role of colleague incivility in linking work-related stressors and job burnout. A cross-sectional study in a sample of faculty administrative employees - Viotti, Sara; Guglielmetti, Chiara; Gilardi, Silvia; Guidetti, Gloria (La Medicina del Lavoro, 2021)
Background: Colleague incivility is one of the subtlest forms of workplace aggression, referring to any low-intensity deviant behavior in violation of the norms of mutual respect with ambiguous intent to harm the target. Although a large corpus of literature has identified the negative consequences of colleague incivility for workers and their organizations, there is a paucity of studies aimed at examining the role played by job characteristics in triggering this form of aggression. The present study, referring to the work environment assumption of Einarsen (2000), proposes that workplace aggression is primarily affected by factors related to deficiencies in the psychosocial work environment. In this view, the present study aimed to test whether the relationships between stressors in the psychosocial work environment (i.e., workload, role conflict, and unfair reward) and burnout (i.e., exhaustion and cynicism) are mediated by colleague incivility. Methods: The study design was cross-sectional and non-randomized. In total, 659 administrative officers employed in a large-sized Italian university completed a self-report questionnaire. Regression and mediation analyses (using the SPSS PROCESS macro) were performed to test the study hypotheses. Findings: After adjusting for control variables (i.e., superior incivility, age, gender, interactions with teaching staff, and interactions with students), the analyses indicated that colleague incivility mediated the associations of role conflict and unfair reward with the two dimensions of burnout. In contrast, the mediating role of colleague incivility in the associations of workload with exhaustion and cynicism was not supported. Discussion: The present study shed light on the key role of colleague incivility in the linkage of variables describing job characteristics and job burnout. From a practical point of view, the present study suggests that in order to prevent colleague incivility, interventions such as job (re)design should be implemented.